Facts About Niacin - R. Elaine Turner; Wendy J. Dahl (EDIS)
Niacin is one of the B vitamins (vitamin B3). Our bodies need niacin to use the energy in carbohydrates, fats, and proteins. Niacin also is needed for DNA repair and for the normal use of calcium in the body. This 2-page fact sheet was written by R. Elaine Turner and Wendy J. Dahl and published by the UF Department of Family Youth and Community Sciences, November 2012.